(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
The 1st International Conference on Science and Sustainable Development (ICSSD 2017) was hosted by the Department of Physics, Covenant University, Ota during June 20-22, 2017 in collaboration with the Abdus Salam Centre for Theoretical Physics (ICTP), Italy. We are grateful to the Management of Covenant University for providing enabling environment for research, and for permitting us to hold the conference. In these proceedings, quality articles that have been peer reviewed by number of experts are presented, which will be useful for government and policymakers. The topics of interest covered by ICSSD 2017 included but were not limited to the following research areas: • Renewable Energy and Environment • Communication/Atmospheric Physics • Radiation and Health/Medical Physics • Agro – Sciences • Earth Sciences/Geology/Geophysics • Science Education • Applied Physics: Innovation and Industry